From the university of professions to the university for development 1953 – 1974 - Pulido Cortés, Óscar; Acuña Rodríguez, Olga Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This article aims at making a critical analysis on those works concerning the process of modernization of the university in Colombia, which emerged in the second half of the 21stcentury, with the implementation of the American model, the American missions’ diagnosis, the education policy reform, and the institutions created in order to change the task of the university of professions to the university for work. The first part of this paper outlines some theoretical and methodological aspects that favor the reading of the researches on modernization of the university in the modernity/coloniality perspective. The second part of this work presents the critical synthesis of researches and papers centered on studying the university in Colombia between 1953 and 1974.